Targeting the Eph/Ephrin System as Anti-Inflammatory Strategy in IBD - Grandi, Andrea; Zini, Irene; Palese, Simone; Giorgio, Carmine; Tognolini, Massimiliano; Marchesani, Francesco; Bruno, Stefano; Flammini, Lisa; Cantoni, Anna Maria; Castelli, Riccardo; Lodola, Alessio; Fusari, Antonella; et al. (Frontiers in Pharmacology, 2019)
Besides their long-known critical role in embryonic growth and in cancer development and progression, EphB (Erythropoietin-producing hepatocellular carcinoma type B) receptor tyrosine kinases and their ephrin-B ligands are involved in the modulation of immune responses and in remodelling and maintaining the integrity of the intestinal epithelial layer. These processes are critically involved in the pathogenesis of inflammatory-based disorders of the gut, like inflammatory bowel diseases (IBDs). Accordingly, our aim was to investigate the role of the EphB/ephrin-B system in intestinal inflammation by assessing the local and systemic effects produced by its pharmacological manipulation in 2,4,6-trinitrobenzenesulfonic acid (TNBS)- (Th1-dependent model) and dextran sulphate sodium (DSS)- (innate response model) induced colitis in mice. To this purpose, we administered chimeric Fc-conjugated proteins, allegedly able to uni-directionally activate either forward (ephrin-B1-Fc) or reverse (EphB1-Fc) signalling, and the soluble monomeric EphB4 extracellular domain protein, that, simultaneously interfering with both signalling pathways, acts as EphB/ephrin-B antagonist. The blockade of the EphB/ephrin-B forward signalling by EphB4 and EphB1-Fc was ineffective against DSS-induced colitis while it evoked remarkable beneficial effects against TNBS colitis: it counteracted all the evaluated inflammatory responses and the changes elicited on splenic T lymphocytes subpopulations, without preventing the appearance of a splice variant of ephrin-B2 gene elicited by the haptenating agent in the colon. Interestingly, EphB4, preferentially displacing EphB4/ephrin-B2 interaction over EphB1/ephrin-B1 binding, was able to promote TNFα release by splenic mononuclear cells in vitro. On the whole, the collected results point to a potential role of the EphB/ephrin-B system as a pharmacological target in intestinal inflammatory disorders and suggest that the therapeutic efficacy of its blockade seemingly works through the modulation of immune responses, independently of changes at the transcriptional and translational level of EphB4 and ephrin-B2 genes.